The influence of stakeholder perspectives on the end-of-life allocation in the life cycle assessment of lithium-ion batteries - Jana Husmann; Jana Husmann; Abdur-Rahman Ali; Abdur-Rahman Ali; Felipe Cerdas; Felipe Cerdas; Christoph Herrmann; Christoph Herrmann (Frontiers in Sustainability, 2023)
With an increasing number of electric vehicles on roads, recycling is an important topic to design circular supply chains for batteries. To stimulate such circular supply chains, the new EU battery directive includes mandatory recycled content in batteries and recovery rates of materials for lithium-ion batteries on the European market. Modeling the end-of-life of batteries as part of a life cycle assessment (LCA) is methodologically challenging as batteries are quite complex product systems. One of these challenges is the allocation of material impacts from different life cycle stages along subsequent product life cycles. We analyzed the different stakeholders in the life cycle of a lithium-ion battery and identified possible LCA questions based on their decision contexts. For each LCA question, an LCA archetype was defined, which includes the functional unit, the system boundary, and the allocation procedure. These archetypes are applied and tested in a case study. The results show a significant variance depending on the archetype used. This highlights the importance of understanding the stakeholder perspective in LCA and decision support.